Evaluation of Mother's Knowledge about Stunting and Observation of Stunting Incidents Based on the Growth of Toddlers at Posyandu Anggrek in Petapahan Village, Lubuk Pakam District, Deli Serdang Regency - Eka Nugraha, Sony; Marianne; Keliat, Jane Melita; Kumar, Manan; Febiola P, Dian; Togatorop, Grace Mutiara (Talenta Publisher, 2023)
This community service aims to provide education about stunting and its prevention in order to increase awareness of mothers so that they can help their children in a period of normal growth and development while reducing the incidence of stunting in Indonesia. This community service activity is carried out by providing counseling related to stunting prevention and filling out questionnaires, especially for mothers who have babies aged 12 months to 5 years at Posyandu Anggrek to determine the effect of this activity on the level of knowledge of mothers regarding stunting issues.The community service carried out is